Pengaruh sudut kemiringan atap seng dan plastik gelombang terhadap tingkat kebisingan akibat air hujan - I. Qiram; G. Rubiono (Dinamika Teknik Mesin, 2016)
Zinc and plastic roofs are used vary widely in poor society because of their low price and their installation easiness. A roof installation with an inclination angle is done in order to the rain water is easy to flow. Rainfall causes noise that has a bad impact to human. This research is aimed to obtaining the effect of inclination angle of zinc and plastic roofs on the noise intensity. The research was done experimentally. The roofs investigated consist of zinc and plastic roofs in waveforms. A room with an overall size of 80 cm x 80 cm x 150 cm was made of wood as the frame. The inclination angles were varied; 10o, 20o, 30o and 40o. The rainfall was modeled by a sprayer with three different water flow rates 0,8; 1,0 and 1,2 lt/s. These flow rates represented low, medium and heavy rains. The noise intensity was measured using a sound level meter, which was placed in the centre of the room. The result shows that increasing the roof inclination angle causes the noise intensity to decrease. The plastic roof has lower noise intensity than the zinc roof. Furthermore, the experimental noise intensity data are relatively safe according to the noise safety level.